Participants' perceptions of a lifestyle approach to promoting physical activity: targeting deprived communities in Kingston-Upon-Hull - Sleap Mike; Waters Heidi; Wormald Helen; Ingle Lee (BMC, 2006)
Abstract Background The health benefits of an active lifestyle have been extensively documented and generally accepted. In the UK, declining physical activity levels are a major contributing factor to a number of public health concerns such as obesity and coronary heart disease. Clearly, there is an urgent need to support people in developing sustainable active lifestyles. In 2003, a new lifestyle-based physical activity service called Active Lifestyles (AL) was set up in Kingston-upon-Hull to help local residents to become more active and develop healthier lifestyles. The service targeted the most deprived communities in the city. The aim of the study was to explore participants' perceptions of the operation and effectiveness of the AL service. Methods Five focus groups were conducted in community centres and offices in the health promotion service in Kingston-upon-Hull. Sixteen white adult males (n = 5) and females (n = 11) participated in the study. Ages ranged from 15-73 years (mean age = 53 years). Data were analysed using a content analysis technique based on the 'framework' approach. Results Three broad themes emerged from the focus groups; the referral process; operational aspects of the AL service; and perceived benefits of the service. Overall, participants were extremely positive about the AL service. Many reported increased activity levels, modified eating habits, and enhanced awareness and education regarding healthier living. Most participants reported that local awareness of the AL service was low and greater promotion was required so more people could benefit. The success of the service was highly dependent upon the qualities and approach of the AL advisor. Conclusion The service appears to have filled a gap in service provision since it offered support to the most sedentary, older, unfit and overweight individuals, many of whom live in the most deprived parts of Kingston-upon-Hull. Traditional exercise referral schemes that focus solely on facility-based exercise should be broadened to encompass everyday lifestyle activity, where referral to a gym or exercise facility is just one of a number of physical activity options.